A self-assembly toolbox for thiophene-based conjugated polyelectrolytes: surfactants, solvent and copolymerisation. Issue 44 (6th November 2017) - Houston, Judith E.; Chevrier, Michèle; Appavou, Marie-Sousai; King, Stephen M.; Clément, Sébastien; Evans, Rachel C.
Abstract : Conjugated polythiophenes are transformed into a range of nanoscale morphologies using simple and versatile self-assembly strategies. Abstract : Targeted control of the aggregation, morphology and optical properties of conjugated polymers is critical for the development of high performance optoelectronic devices. Here, self-assembly approaches are used to strategically manipulate the order, conformation and spatial distribution of conjugated polymers in solution and subsequently prepared thin films. The supramolecular complex organisation of phosphonium-functionalised homo- (P3HTPMe3 ) and diblock (P3HT- b -P3HTPMe3 ) ionic conjugated polythiophenes upon solvent-mediation and co-assembly with oppositely charged surfactants is investigated. UV/Vis absorption and photoluminescence spectroscopies, small-angle neutron scattering (SANS), cryo-transmission electron microscopy (cryo-TEM) and atomic force microscopy (AFM) are used to probe the organisation and photophysical response of the aggregates formed. Subtle differences in the surfactant mole fraction and structure, as well as the solvent polarity, yield differences in the nature of the resultant homopolyelectrolyte-surfactant complexes. In contrast, only moderate structural transformations are observed for the amphiphilic diblock copolyelectrolyte, emphasising the structure "anchoring" effect of a neutral polymer block when amphiphilic copolymers are dissolved in polar solvents. These results highlight the versatility of self-assembly to access a range of nanomorphologies, which could be crucial for the design of the next generation of organic optoelectronic devices.